Depression in elders of a Long Stay Institution - Maíra Rossetto; Katia Smaniotto Maia; Vanessa Cervi Da Silva; Éder Campos Pinto; Susane Flores Cosentino; Maria da graça Soller Rodrigues (Universidade Federal de Santa Maria, 2012)
Objective: to determine the prevalence of depression in elderly residents of a Long Stay Institution for Aged. Method: this is a descriptive study transverse, of quantitative approach. The population consisted of 48 subjects. To assess the mental state was used Mini Mental State Examination and collection of data to the Geriatric Depression Scale (GDS-15). Were ethical principles contained in Resolution 196/96 of the National Health. Results: results showed that 25% of the elderly showed no signs of depression, 43.75% showed signs of depression, mild/moderate and 31.25% showed signs of severe depression. The prevalence of depression was higher in women (55.5%) than men (44.5%). Conclusion: high levels of depression in the sample report identified the need for psychological support planning can provide a better quality of life for residents in institution studied as well as warn of similar prevalence in the general ILPIs